Bioerosion traces on titanosaurian sauropod bones from the Upper Cretaceous Marília Formation of Brazil - Paes Neto, Voltaire Dutra (2018)
Bone bioerosions provide an important taphonomic record on fossils from continental deposits dating back to the late Paleozoic. The morphological diversity of bone bioerosions is especially high in vertebrate remains from the Late Cretaceous. Here we describe four morphotypes of bioeroson preserved on titanosaur dinosaur bones collected from the Maastrichtian Marília Formation of Brazil. These traces differ from previously described ichnotaxa, and include branching furrows and surface removal resembling insect bioerosions, channels with semicircular cross-sections consistent with either root etchings or insects, and bite traces left by vertebrates. Taphonomic sequencing shows that time-averaging was an important aspect in the genesis of the Marília Formation taphocoenosis and demonstrates that traces left on bones are significant tools for reconstructing Late Cretaceous ecosystems.